2021
DOI: 10.1182/blood.2020007445
|View full text |Cite
|
Sign up to set email alerts
|

Tumor interferon signaling and suppressive myeloid cells are associated with CAR T-cell failure in large B-cell lymphoma

Abstract: Axicabtagene ciloleucel (axi-cel) is a chimeric antigen receptor (CAR) T cell therapy for relapsed or refractory large B cell lymphoma (LBCL). Here, we evaluated whether immune dysregulation, present prior to CAR-T cell therapy, associated with treatment failure. Tumor expression of interferon (IFN) signaling, high blood levels of monocytic myeloid-derived suppressor cells (M-MDSCs), and high blood IL-6 and ferritin each associated with a lack of durable response. Similar to other cancers, we found that in LBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
138
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 162 publications
(162 citation statements)
references
References 59 publications
5
138
3
2
Order By: Relevance
“…The differential expression analysis (16 patients with also WGS data available) showed a higher expression level of genes known to be target of tumor signaling in patients treated with CAR-19 (Figure 4c). Interestingly, the ISG.RS signature, previously described to be associated with Tcell exhaustion and worse outcome after immunotherapy 12,48 , was enriched in r/r patients harboring at least one reported genomic driver (Figure 4d), while the INFG.GS signature, associated with higher response to check point blockade, was enriched in patients without any significant genomic drivers (Supplementary Figure 6). Moreover, the cases containing at least one reported genomic driver were characterized by higher MTV, reflecting the relationship between disease aggressiveness and the TME (Figure 4e).…”
Section: Chromothripsis Events Mark Cases Doomed To Fail Car-19 Treatmentmentioning
confidence: 84%
See 3 more Smart Citations
“…The differential expression analysis (16 patients with also WGS data available) showed a higher expression level of genes known to be target of tumor signaling in patients treated with CAR-19 (Figure 4c). Interestingly, the ISG.RS signature, previously described to be associated with Tcell exhaustion and worse outcome after immunotherapy 12,48 , was enriched in r/r patients harboring at least one reported genomic driver (Figure 4d), while the INFG.GS signature, associated with higher response to check point blockade, was enriched in patients without any significant genomic drivers (Supplementary Figure 6). Moreover, the cases containing at least one reported genomic driver were characterized by higher MTV, reflecting the relationship between disease aggressiveness and the TME (Figure 4e).…”
Section: Chromothripsis Events Mark Cases Doomed To Fail Car-19 Treatmentmentioning
confidence: 84%
“…In this scenario, the CAR-T cells act as a gateway into the immunosuppressed TME to allow the host immune system to destroy the tumor. Data from axi-cel-treated patients showed that patients with high serum inflammatory markers, along with increased tumor IFN signaling were indicative of lack of durable response 12 . Recent studies by Alizadeh et al 53 demonstrated that CAR-T cells secrete IFN gamma and activate host T cells in a mouse model of glioblastoma and these cells preserved their anti-tumor activity also when infused without CAR-T.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With their heterogeneous range of suppressive mechanisms, myeloid cells have become a major target to consider for combinatorial approaches with CAR T cells, checkpoint inhibitors, and NK cell-based therapies. Indeed, it has been demonstrated that not only do myeloid phenotypes positively correlate with CAR T therapy failure [159], but also that ablation of these populations can improve antitumor effects of various immunotherapeutics [160][161][162][163]. Strategies to overcome myeloid-mediated suppression of the immune response can be generally categorized into (1) prevention of recruitment to the tumor, (2) depletion of myeloid populations or disruption of their suppressive mechanisms, and (3) repolarization towards immunostimulatory phenotypes.…”
Section: Therapeutic Strategies To Target Suppressive Myeloid Cellsmentioning
confidence: 99%